A simple business-cycle model with Schumpeterian features - Luís F. Costa; Huw D. Dixon (Cardiff University, Cardiff Business School, 2007)
We develop a dynamic general equilibrium model of imperfect competition where a sunk cost of creating a new product regulates the type of entry that dominates in the economy: new products or more competition in existing industries. Considering the process of product innovation is irreversible, introduces hysteresis in the business cycle. Expansionary shocks may lead the economy to a new `prosperity plateau,' but contractionary shocks only affect the market power of mature industries.
Keywords: E62; L13; L16; 330; Entry; Hysteresis; Mark-up; Konjunktur; Unvollkommener Wettbewerb; Dynamisches Gleichgewicht; Sunk Costs; Innovation; Theorie